Efeito da deposição de nitrogênio sobre o metabolismo, o incremento de biomassa e a riqueza de espécies em uma comunidade de gramíneas do cerrado - Ferreira, Ana Maria (2017)
Anthropogenic activities contribute to increased annual nitrogen deposition, thereby researchers have been working with models that estimate its long-term impact in order to predict changes in terrestrial ecosystems. The present study was directed to nitrogen deposition in the year 2050, aiming to analyze how a community of grasses in Brazilian Cerrado, composed by C3 and C4 species, would behave in this scenario. For this purpose, the species present in the site were identified, had their photosynthetic metabolism determined and their biomass by tiller and total biomass accounted for in the three treatments to which they were submitted (control, low and high nitrogen supplementation). Twenty-one species were found in the study area, of which 15 were identified and had their photosynthetic metabolism determined. Only Echinolaena inflexa was determined as C3, while all other species were C4. The results showed that the increase of nitrogen deposition rates favored biomass increment in some species to the detriment of others, reducing the species number. One C3 and two C4 species were selected in an attempt to understand nitrogen effect in their photosynthetic metabolism. Therefore, analyzes of leaf and stem carbohydrate content, leaf nitrogen content, photosynthetic performance, specific leaf area and relative water content were performed. The C3 species showed better nitrogen utilization than the C4 ones, developing better in a pessimistic scenario. However, C4 species dominance in Brazilian Cerrado could impair the development of the C3 grass species, since the first ones are excellent competitors. The exotic species Urochloa decumbens represented very well this situation in this study.